THE PHENOMENON OF CHILDFREE IN INDONESIA IN THE PERSPECTIVE OF MAQASID AL-SYARIAH - Afrianto (International Journal of Islamic Studies, 2025)
The phenomenon of childfree in Indonesia has become a topic that attracts attention, especially among Muslim communities facing the challenges of modernization, social change, and the dynamics of urban life. This study aims to analyze the phenomenon of childfree from the perspective of maqasid al-syariah, which is the objectives of sharia in Islam. In this context, marriage is not only seen as a biological bond between a man and a woman, but also as a means to maintain the continuity of humanity and produce quality offspring. The results show that although the choice not to have children can be understood as a form of individual freedom, this is contrary to the principles of maqasid al-syariah which emphasize the importance of preserving offspring and achieving benefits for society. In Islam, marriage has broader goals, including forming a generation that is pious and God-fearing, and contributing to the welfare of society. The childfree phenomenon also reflects society’s changing values and views on marriage and family, with many couples choosing to focus on their careers, personal freedom and quality of life. This choice is often fueled by concerns about the unstable state of the world and the challenges of raising children. As such, this phenomenon needs to be critically considered in the context of Islamic values and its impact on social structures. This research is expected to provide deeper insights into the social and cultural implications of childfree choices and encourage further discussion on marriage, offspring, and social responsibility from an Islamic perspective.